Pembuatan Aplikasi Media Interaktif Untuk Pengenalan Tokoh Alkitab Berbasis Android - Valentine Grieda Sahuburua; Kristo Radion Purba; Anita Nathania Purbowo (Jurnal Infra, 2016)
Facilities which parent provide in the form of gadgets are not infrequently abused by the child. Gadgets that can be used as a supporting medium children to learn more commonly used as a medium of entertainment, such as games. In the current era, it is not rare to find that people are not too interested in reading the Bible. Not only in the adult population, but also in teenagers and children. Children tend to only know one or two salient life stories of Bible characters. As to the character of David, the children tend to recognize David as someone who beat Goliath the Philistine commander. But other than that, most children do not know the story of David's life more.This application is an interactive media that can be used by children to be able to recognize the biblical figures like David and Joseph. At each stage of the application that requires a reference to the Bible, has been provided so that children can directly read the reference and can also play this application. Overall this application helps children get to know the Bible figure better. The application used to create interactive media are Android Studio and supported by AndEngine.